Array comparative genomic hybridization with cyanin cis-platinum-labeled DNAs - Anton K. Raap; Marja J.M. van der Burg; Jeroen Knijnenburg; Eric Meershoek; Carla Rosenberg; Joe W. Gray; Joop Wiegant; J. Graeme Hodgson; Hans J. Tanke (BioTechniques)
Fluorescent cis-platinum compounds that react with the N7 atom of guanine are useful for labeling nucleic acids in fluorescence hybridization applications. Here we report that cyanin (CyN) cis-platinum labeling of DNA samples for array comparative genomic hybridizations (arrayCGH) can be achieved reproducibly and reliably. We demonstrate that degrees of labeling of approximately 1% of all nucleotides in test and reference DNA samples with CyN3- and CyN5-cis-platinum produces arrayCGH signal-to-background ratios ranging from 30 to 40. The arrayCGH results achieved during analyses of mouse and human tumor samples were comparable to those achieved using enzymatic labeling. Thus, we conclude that Cy-cis-platinum labeling is an alternative to enzymatic labeling for arrayCGH.